FAKTOR RISIKO ASUPAN ENERGI DAN RIWAYAT PENYAKIT INFEKSI TERHADAP STUNTING PADA BALITA 24-59 BULAN - Latifahanun, Este; Kartini, Apoina; Budhi R, Kamilah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2021)
Stunting is a condition of a child’s height below normal ( 2SD)  based on nutritional status according to WHO child growth standard, Indicates chronic malnutrition in early growth and development of life. In 2017, around 150,8 million children under five in the world were stunted, half of children from Asia (55%), while 39% live in Africa. The desaign of this research used a case control study. The population this study was all children aged 24-59 month in Guntur I health center. Sampling techniques using simple random sampling amounted to 32 case and 32 control, data were analyzed with Chi-Square. The results of the study showed that energy intake was a risk factor for stunting (p value 0,012 OR 4,259 95%CI 1,488-12,192) and infection desease is not a risk factor for stunting (p value 0,080 OR 4,324 95%CI 1,010,462-7,643). The results of the overall analysis showed that low intake energy was a risk factor for stunting in children aged 24-59 month.